Preparation method of composite adsorption desulfurizer
By combining metal organic frame materials (MOFs) with mesoporous alumina, composite adsorbents with high adsorption capacity and selectivity were prepared, which solved the problem of poor removal of thiophene sulfides in the existing oil pin desulfurization technology, and achieved a more efficient and economical desulfurization effect.
Patent Information
- Application Number
- CN202510205778.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-25
- Publication Date
- 2025-04-25
AI Technical Summary
The existing oil pin desulfurization technology has problems such as poor removal effect of thiophene sulfides, harsh reaction conditions, high equipment investment and operating costs, and the selectivity and adsorption capacity of the adsorbent are insufficient, making it difficult to achieve efficient recycling.
The composite adsorbent is prepared by chemical bonding method by compounding metal organic frame materials (MOFs) to enhance its selectivity and adsorption capacity to sulfides, and improve sulfur selectivity through functionalization sites.
It significantly improves the adsorption capacity and selectivity of the adsorbent, enhances the stability and circulation performance of the material, reduces the cost of use, and expands the scope of high-temperature application.
Smart Images

Figure BDA0005284486730000071 
Figure BDA0005284486730000072
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a composite adsorbent used for deep desulfurization of oil products. Background Art
[0002] With the rapid development of the global economy and the acceleration of the industrialization process, the demand for oil as an important energy source and chemical raw material continues to grow. However, oil generally contains sulfides, which will be converted into sulfur dioxide (SO2) during the combustion process, leading to environmental problems such as acid rain and haze, seriously endangering the ecological environment and human health. In addition, sulfides will also corrode oil processing equipment, affect catalyst activity, and reduce oil quality. Therefore, the research and application of oil desulfurization technology is of great significance to environmental protection, energy utilization and industrial production.
[0003] Traditional oil desulfurization technologies mainly include hydrodesulfurization (HDS) and non-hydrodesulfurization. Hydrodesulfurization technology converts sulfides into hydrogen sulfide (H2S) and separates them under high temperature and high pressure conditions under the action of a catalyst. It has the advantages of high desulfurization efficiency and a wide range of applications. It is currently the most widely used desulfurization technology in industry. However, hydrodesulfurization technology also has some limitations, such as poor removal of thiophene sulfides, harsh reaction conditions, high equipment investment and operating costs. Non-hydrodesulfurization technologies include oxidative desulfurization, extractive desulfurization, biological desulfurization and adsorption desulfurization. Among them, adsorption desulfurization technology has received widespread attention in recent years due to its mild operating conditions, low energy consumption and simple equipment.
[0004] Adsorption desulfurization technology is a method of separating sulfides from oil products by selectively adsorbing sulfides in oil products by adsorbents. The key to adsorption desulfurization technology is to develop efficient and highly selective adsorbents. An ideal adsorbent should have the following characteristics: high specific surface area and porosity to provide sufficient adsorption sites; strong adsorption capacity and high selectivity for sulfides to reduce the adsorption of other components; good regeneration performance to achieve the recycling of adsorbents; and low cost and environmental friendliness.
[0005] In recent years, researchers have developed various types of adsorbents for oil desulfurization, including activated carbon, molecular sieves, metal oxides, metal organic framework materials (MOFs), etc. Activated carbon has a high specific surface area and rich pore structure, but its selectivity for sulfides is poor and its regeneration performance is poor. Molecular sieves have regular pore structures and adjustable pore sizes. Metal ions can be introduced through ion exchange to improve the adsorption performance of sulfides, but their adsorption capacity is limited. Metal oxides such as zinc oxide and copper oxide have strong chemical adsorption effects on sulfides, but their adsorption rate is slow and they are easily contaminated by other components in oil. MOFs are a type of porous material formed by metal ions or clusters connected to organic ligands through coordination bonds. They have high specific surface area, adjustable pore size and functionalized sites, and show great application potential in the field of adsorption desulfurization.
[0006] Among these adsorbents, activated carbon and molecular sieves have a variety of pore sizes, and mesoporous alumina is a new type of material after zeolite molecular sieves. It is a porous material with nanometer particle size, high specific surface area, suitable pore structure, narrow pore size distribution and good surface acidity. It can be used as an adsorbent, catalyst or catalyst carrier and is widely used in various energy and chemical fields. With the development of material science research, many new microporous materials and mesoporous materials have been synthesized. Among the new materials, MOFs have become excellent materials in the field of oil refining because they have better surface area, pore volume and pore structure than traditional adsorbents.
[0007] Although adsorption desulfurization technology has made significant progress, it still faces some challenges. For example, how to improve the selectivity and adsorption capacity of adsorbents for sulfides, how to achieve efficient regeneration and recycling of adsorbents, and how to reduce the cost of adsorbents. In the future, with the continuous development of new materials and technologies, adsorption desulfurization technology is expected to play a more important role in the field of oil desulfurization and contribute to the realization of clean energy and sustainable development goals.
[0008] The research on oil adsorption desulfurization technology has important practical significance and broad application prospects. By continuously developing new and efficient adsorbents, optimizing adsorption processes, and improving the efficiency and economy of adsorption desulfurization, it will provide strong support for solving the problem of oil desulfurization, protecting the ecological environment, and promoting the clean use of energy. Summary of the invention
[0009] Mesoporous alumina is an ideal adsorption material due to its high specific surface area, narrow pore size distribution, ordered pore structure and large adsorption capacity. Therefore, it is often used as a solid adsorbent and has potential application value in the field of selective adsorption. The controllable synthesis of the morphology and size of mesoporous alumina makes its application more and more extensive.
[0010] On the other hand, metal organic framework materials (MOFs) have advantages such as high specific surface area, adjustable pore structure and functionalized sites. The ultra-high specific surface area and pore structure of MOFs can provide a large number of physical adsorption sites, which can adsorb sulfide molecules through forces such as van der Waals forces. Moreover, the metal nodes or functionalized sites in MOFs can undergo chemical reactions such as coordination and acid-base reactions with sulfide molecules to achieve chemical adsorption. In addition, for sulfides containing aromatic rings (such as thiophene compounds), the organic ligands in MOFs can adsorb sulfide molecules through π-π interactions. Therefore, it shows great application potential in the field of adsorption desulfurization.
[0011] The present invention relates to a method for preparing a metal organic framework material-mesoporous alumina composite adsorbent for deep desulfurization of oil products. The technical solution of the present invention is:
[0012] The first step is to activate the surface of mesoporous alumina: add the mesoporous alumina to a 5% dilute hydrochloric acid solution, immerse for 24 hours, and treat the mesoporous alumina with an acid method; then filter, and then add the mesoporous alumina to 10% hydrogen peroxide for oxidation activation, and filter after activation for 10 hours; then vacuum dry at 100°C to obtain substrate A;
[0013] The second step is the chemical grafting activation treatment on the surface of mesoporous alumina: prepare an ethanol solution of 4-mercaptopyridine with a mass fraction of 2%, and take a 4-mercaptopyridine ethanol solution according to the ratio of 4-mercaptopyridine to 5% of the mass of matrix A; then add matrix A into the 4-mercaptopyridine ethanol solution and perform ultrasonic treatment for 2 hours to obtain a mesoporous alumina with a rich surface of grafting active sites, which is recorded as matrix B;
[0014] The third step is material mixing: dissolving aromatic dicarboxylic acid and polyvinyl pyrrolidone in DMF, adding the main metal salt required for the reaction, stirring until dissolved, then adding rare earth metal salt as a regulating metal, stirring evenly, and adding a certain mass of matrix B; stirring the mixture for 6 hours to obtain a material mixture;
[0015] The fourth step is to prepare a metal organic-mesoporous alumina composite adsorbent by an in-situ synthesis method: pour the material mixture of the third step into a reactor with a tetrafluoroethylene liner, and place the reactor in a reaction box with a program heating function; heat it to 130°C at a rate of 10°C / h, and react at this temperature for 8h; after the reaction is completed, allow the reactor to cool naturally to room temperature to obtain a gray precipitate; filter and wash the precipitate three times with DMF, wash it twice with CH2Cl2 and filter it, and then dry it at 120°C under vacuum conditions for 8h to obtain a metal organic framework material-mesoporous alumina composite adsorbent;
[0016] In the third step, the aromatic dicarboxylic acid is 4,4'-biphenyl dicarboxylic acid, the mass ratio of the aromatic dicarboxylic acid to the metal salt is 1:2-8; the mass ratio of the aromatic dicarboxylic acid to the polyvinyl pyrrolidone is 1:20-40; the mass content of the aromatic dicarboxylic acid in DMF is 1%-10%;
[0017] In the third step, the main metal salt is zinc nitrate; the amount of the main metal salt added is controlled according to the mass ratio of the main metal salt to the mass of the matrix B being 1:10-100.
[0018] In the third step, the rare earth metal salt is a nitrate of a rare earth metal, the rare earth metal is one or more of cerium, yttrium, and lanthanum, and the amount of the rare earth metal salt added is calculated as 5% of the amount of Zn.
[0019] Compared with the prior art, the present invention has the following innovations:
[0020] (1) The method of preparing MOFs and alumina composite materials by chemical bonding is innovative. After alumina is activated, 4-mercaptopyridine is bonded to the hydroxyl groups on the surface of alumina and linked to the outer surface of alumina and the inner surface of the pores. In the in-situ synthesis of MOFs on alumina, the core reaction is the self-assembly of aromatic dicarboxylic acid organic ligands and metals to form porous MOFs materials. During the self-assembly, the pyridine ring of 4-mercaptopyridine has the ability to coordinate with the metal, and 4-mercaptopyridine and MOFs are bonded, realizing the chemical bonding of MOFs materials and carriers.
[0021] (2) After chemical bonding treatment, MOFs and mesoporous alumina are linked to form a composite material through mercapto bipyridine chemical bonds, which significantly improves the composite rate of the two materials and enhances the stability of MOFs. In addition, the use of rare earth metals such as cerium, yttrium, and lanthanum as modified metals can transform the structure of MOFs materials and form sulfide adsorption active points. The preparation of MOFs and alumina composite materials through innovative chemical bonding methods has significant advantages in obtaining adsorbents.
[0022] Technical advantages and features of the present invention:
[0023] Metal-organic frameworks (MOFs) and mesoporous alumina composites combine the unique advantages of both materials and show great application prospects in fields such as adsorption desulfurization.
[0024] (1) Synergistically enhance adsorption desulfurization performance:
[0025] The composite material has a high specific surface area and porosity because MOFs itself has an ultra-high specific surface area and an adjustable pore structure, and mesoporous alumina also has a rich mesoporous structure. After the two are combined, the specific surface area and porosity of the material can be further increased, providing more adsorption sites, thereby significantly improving the adsorption capacity of the target molecules.
[0026] The sulfur adsorption capacity of materials can be improved through multiple adsorption mechanisms. MOFs can adsorb target molecules through coordination bonds, π-π stacking and other forces, while mesoporous alumina can adsorb molecules through physical adsorption and surface hydroxyl groups. After the two are combined, they can play a synergistic effect, achieve multiple adsorption of sulfur molecules, and improve adsorption efficiency and selectivity.
[0027] In addition, the composite material improves sulfur selectivity through functionalized sites. The organic ligands of MOFs can be functionalized and modified to introduce transition metal functional groups, thereby achieving selective adsorption of sulfur molecules with specific structures. The surface of mesoporous alumina can also be modified to further improve its selectivity for adsorbing sulfur molecules.
[0028] (2) Good stability and cycle performance:
[0029] The mechanical stability of the composite material can be significantly enhanced. The addition of mesoporous alumina can improve the mechanical strength of the composite material, especially the MOFs material, and prevent the collapse of the MOFs structure, thereby improving the stability and recycling performance of the material.
[0030] The thermal stability of the composite material is also improved. Mesoporous alumina has high thermal stability, which can protect MOFs from high temperatures and expand the high-temperature application range of the composite material.
[0031] Since the pore size of mesoporous materials is large and easy to diffuse, the composite material is easy to regenerate after adsorption saturation. The composite material can be regenerated by simple heat treatment or solvent washing to restore its adsorption performance and reduce the cost of use.
[0032] (3) Flexible material design enables multi-angle expansion:
[0033] The structure and properties of MOFs and mesoporous alumina can be designed and regulated to obtain composite materials with specific functions. This composite material has broad application prospects in the fields of sulfide adsorption and separation in oil and gas.
[0034] In summary, MOFs materials and mesoporous alumina composites combine the advantages of the two materials, and have the advantages of synergistically enhanced adsorption performance, good stability and cycle performance. They are a new type of adsorption desulfurization functional material with great development prospects.
[0035] Application Example 1:
[0036] The first step is to activate the surface of mesoporous alumina: add the mesoporous alumina to a 5% dilute hydrochloric acid solution, immerse for 24 hours, and treat the mesoporous alumina with an acid method; then filter, and then add the mesoporous alumina to 10% hydrogen peroxide for oxidation activation, and filter after activation for 10 hours; then vacuum dry at 100°C to obtain substrate A;
[0037] The second step is the chemical grafting activation treatment on the surface of mesoporous alumina: prepare an ethanol solution of 4-mercaptopyridine with a mass fraction of 2%, and take a 4-mercaptopyridine ethanol solution according to the ratio of 4-mercaptopyridine to 5% of the mass of matrix A; then add matrix A into the 4-mercaptopyridine ethanol solution and perform ultrasonic treatment for 2 hours to obtain a mesoporous alumina with a rich surface of grafting active sites, which is recorded as matrix B;
[0038] The third step is material mixing: dissolving aromatic dicarboxylic acid and polyvinyl pyrrolidone in DMF, adding the main metal salt required for the reaction, stirring until dissolved, then adding rare earth metal salt as a regulating metal, stirring evenly, and adding a certain mass of matrix B; stirring the mixture for 6 hours to obtain a material mixture;
[0039] The fourth step is to prepare a metal organic-mesoporous alumina composite adsorbent by an in-situ synthesis method: pour the material mixture of the third step into a reactor with a tetrafluoroethylene liner, and place the reactor in a reaction box with a program heating function; heat it to 130°C at a rate of 10°C / h, and react at this temperature for 8h; after the reaction is completed, allow the reactor to cool naturally to room temperature to obtain a gray precipitate; filter and wash the precipitate three times with DMF, wash it twice with CH2Cl2 and filter it, and then dry it at 120°C under vacuum conditions for 8h to obtain a metal organic framework material-mesoporous alumina composite adsorbent;
[0040] In the third step, the aromatic dicarboxylic acid is 4,4'-biphenyl dicarboxylic acid, the mass ratio of the aromatic dicarboxylic acid to the metal salt is 1:4; the mass ratio of the aromatic dicarboxylic acid to polyvinyl pyrrolidone is 1:30; the mass content of the aromatic dicarboxylic acid in DMF is 2%;
[0041] In the third step, the main metal salt is zinc nitrate; the amount of the main metal salt added is controlled according to the mass ratio of the main metal salt to the mass of the matrix B being 1:20.
[0042] In the third step, the rare earth metal salt is a nitrate of a rare earth metal, the rare earth metal is cerium, and the amount of the added rare earth metal salt is calculated as 5% of the amount of Zn.
[0043] Application Example 1:
[0044] The first step is to activate the surface of mesoporous alumina: add the mesoporous alumina to a 5% dilute hydrochloric acid solution, immerse for 24 hours, and treat the mesoporous alumina with an acid method; then filter, and then add the mesoporous alumina to 10% hydrogen peroxide for oxidation activation, and filter after activation for 10 hours; then vacuum dry at 100°C to obtain substrate A;
[0045] The second step is the chemical grafting activation treatment on the surface of mesoporous alumina: prepare an ethanol solution of 4-mercaptopyridine with a mass fraction of 2%, and take a 4-mercaptopyridine ethanol solution according to the ratio of 4-mercaptopyridine to 5% of the mass of matrix A; then add matrix A into the 4-mercaptopyridine ethanol solution and perform ultrasonic treatment for 2 hours to obtain a mesoporous alumina with a rich surface of grafting active sites, which is recorded as matrix B;
[0046] The third step is material mixing: dissolving aromatic dicarboxylic acid and polyvinyl pyrrolidone in DMF, adding the main metal salt required for the reaction, stirring until dissolved, then adding rare earth metal salt as a regulating metal, stirring evenly, and adding a certain mass of matrix B; stirring the mixture for 6 hours to obtain a material mixture;
[0047] The fourth step is to prepare a metal organic-mesoporous alumina composite adsorbent by an in-situ synthesis method: pour the material mixture of the third step into a reactor with a tetrafluoroethylene liner, and place the reactor in a reaction box with a program heating function; heat it to 130°C at a rate of 10°C / h, and react at this temperature for 8h; after the reaction is completed, allow the reactor to cool naturally to room temperature to obtain a gray precipitate; filter and wash the precipitate three times with DMF, wash it twice with CH2Cl2 and filter it, and then dry it at 120°C under vacuum conditions for 8h to obtain a metal organic framework material-mesoporous alumina composite adsorbent;
[0048] In the third step, the aromatic dicarboxylic acid is 4,4'-biphenyl dicarboxylic acid, the mass ratio of the aromatic dicarboxylic acid to the metal salt is 1:2-8; the mass ratio of the aromatic dicarboxylic acid to polyvinyl pyrrolidone is 1:15; the mass content of the aromatic dicarboxylic acid in DMF is 3%;
[0049] In the third step, the main metal salt is zinc nitrate; the amount of the main metal salt added is controlled according to the mass ratio of the main metal salt to the mass of the matrix B being 1:30.
[0050] In the third step, the rare earth metal salt is a nitrate of a rare earth metal, the rare earth metal is cerium, and the amount of the added rare earth metal salt is calculated as 5% of the amount of Zn.
[0051] Comparative Example 1:
[0052] Untreated mesoporous alumina was dried at 100° C. for 2 h and used as comparative example 1 for an adsorption desulfurization agent.
[0053] Comparative Example 2:
[0054] The first step is to activate the surface of mesoporous alumina: add the mesoporous alumina to a 5% dilute hydrochloric acid solution, immerse for 24 hours, and treat the mesoporous alumina with an acid method; then filter, and then add the mesoporous alumina to 10% hydrogen peroxide for oxidation activation, and filter after activation for 10 hours; then vacuum dry at 100° C. to obtain Comparative Example 2;
[0055] Comparative Example 3
[0056] The preparation method is similar to that of Application Example 1, except that 4,4'-biphenyldicarboxylic acid is replaced by 4-biphenylcarboxylic acid during the preparation process, and the other steps and reagents are the same as those of Application Example 1.
[0057] Evaluation of adsorption desulfurization performance
[0058] Laboratory evaluation method for adsorption desulfurization performance of metal organic-mesoporous alumina composite adsorbent:
[0059] A certain amount of thiophene was dissolved in n-heptane to obtain a simulated sulfur-containing oil product, and the sulfur content of the simulated oil product was controlled to be 500 μg / g. Then the desulfurization performance of the adsorbent was tested by the static adsorption method. A certain mass of adsorbent was weighed, and a certain volume of simulated oil was measured according to the mass ratio of adsorbent to oil of 1:10 and placed in a closed round-bottom flask. Stirring was performed at 25°C for 2 hours, and then stirring was stopped. The sample was taken after standing. The sulfur content in the sample was tested by gas chromatography, and the desulfurization rate of the adsorbent was calculated according to the following formula.
[0060] Desulfurization rate formula:
[0061]
[0062] Where N0 and Nt are the sulfur contents of the simulated oil before and after desulfurization, respectively.
[0063] Table 1 Desulfurization effect of comparative examples and application examples on simulated oil products and actual oil products
[0064]
[0065] From the above results, it can be seen that the order of desulfurization performance is Application Examples 1 and 2 > Comparative Examples 2 and 3 > Comparative Example 1, which shows that the structure of the prepared metal organic-mesoporous alumina composite adsorbent is novel, and MOFs itself has an ultra-high specific surface area and an adjustable pore structure, and mesoporous alumina also has a rich mesoporous structure. After the two are combined, the specific surface area and porosity of the material can be further increased, providing more desulfurization adsorption sites, thereby significantly improving the adsorption capacity for the target molecules.
Claims
1. A method for preparing a metal organic framework material-mesoporous alumina composite adsorbent for deep desulfurization of oil products. The technical solution of the present invention is: The first step is to activate the surface of mesoporous alumina: add the mesoporous alumina to a 5% dilute hydrochloric acid solution, immerse for 24 hours, and treat the mesoporous alumina with an acid method; then filter, and then add the mesoporous alumina to 10% hydrogen peroxide for oxidation activation, and filter after activation for 10 hours; then vacuum dry at 100°C to obtain substrate A; The second step is the chemical grafting activation treatment on the surface of mesoporous alumina: prepare an ethanol solution of 4-mercaptopyridine with a mass fraction of 2%, and take a 4-mercaptopyridine ethanol solution according to the ratio of 4-mercaptopyridine to 5% of the mass of matrix A; then add matrix A into the 4-mercaptopyridine ethanol solution and perform ultrasonic treatment for 2 hours to obtain a mesoporous alumina with a rich surface of grafting active sites, which is recorded as matrix B; The third step is material mixing: dissolving aromatic dicarboxylic acid and polyvinyl pyrrolidone in DMF, adding the main metal salt required for the reaction, stirring until dissolved, then adding rare earth metal salt as a regulating metal, stirring evenly, and adding a certain mass of matrix B; stirring the mixture for 6 hours to obtain a material mixture; The fourth step is to prepare a metal organic-mesoporous alumina composite adsorbent by an in-situ synthesis method: pour the material mixture of the third step into a reactor with a tetrafluoroethylene liner, and place the reactor in a reaction box with a program heating function; heat it to 130°C at a rate of 10°C / h, and react at this temperature for 8h; after the reaction is completed, allow the reactor to cool naturally to room temperature to obtain a gray precipitate; filter and wash the precipitate three times with DMF, wash it twice with CH2Cl2 and filter it, and then dry it at 120°C under vacuum conditions for 8h to obtain a metal organic framework material-mesoporous alumina composite adsorbent; In the third step, the aromatic dicarboxylic acid is 4,4'-biphenyldicarboxylic acid, and the mass ratio of the aromatic dicarboxylic acid to the metal salt is 1:2-8; the mass ratio of the aromatic dicarboxylic acid to polyvinyl pyrrolidone is 1:20-40; the mass content of the aromatic dicarboxylic acid in DMF is 1%-10%; the main metal salt is zinc nitrate; the amount of the main metal salt added is controlled according to the mass ratio of the main metal salt to the matrix B of 1:10-100; the rare earth metal salt is a nitrate of a rare earth metal, the rare earth metal is one or more of cerium, yttrium, and lanthanum, and the amount of the rare earth metal salt added is calculated as 5% of the amount of Zn substance.